China's central bank digital currency : what it means for ASEAN - Randhawa, Dipinder Singh (2021)
The People’s Bank of China (PBOC) is at an advanced stage of conducting pilot studies with its digital currency. What will a digital yuan entail domestically for China, and what concerns and opportunities could it create for ASEAN?